2015
DOI: 10.1007/s00784-015-1555-8
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative endodontic procedure of an infected immature permanent human tooth: an immunohistological study

Abstract: REP of an immature permanent infected tooth may heal the periapical infection and may result in a combination of regeneration and repair of the pulp-dentin complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
53
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 35 publications
4
53
0
1
Order By: Relevance
“…Concerning the state of the pulp before the initiation of regenerative treatment, two teeth displayed irreversible pulpitis , nine had pulpal necrosis , and ten had apical periodontitis . Two teeth were completely healthy, and their pulps were extirpated , while one had previously initiated root canal treatment and lacked pulp tissue .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the state of the pulp before the initiation of regenerative treatment, two teeth displayed irreversible pulpitis , nine had pulpal necrosis , and ten had apical periodontitis . Two teeth were completely healthy, and their pulps were extirpated , while one had previously initiated root canal treatment and lacked pulp tissue .…”
Section: Resultsmentioning
confidence: 99%
“…Then, 43 studies were excluded by title and 32 studies were excluded by abstract. Finally, 12 articles met the inclusion criteria after full‐text evaluation .…”
Section: Resultsmentioning
confidence: 99%
“…However, histologic analyses after revitalization show that in some cases healing or repair might take place but not regeneration. Repair is defined as ectopic tissue formation with a partial loss of function with studies reporting the formation of fibrous tissue, cementum or bone inside the root canal (da Silva et al 2010, Wang et al 2010, Martin et al 2014, Meschi et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…However, current endodontic interventions, such as root canal treatments, are based on the use of rubber cones and liquid sealants as filling biomaterials that do not promote tissue regeneration (Guldener, ), although regenerative endodontic procedures, such as apexogenesis and maturogenesis, have recently been explored. Newer reports (Meschi et al , ) have demonstrated that regenerative endodontic procedure techniques are not able to induce the regeneration of pulp tissues. Instead, the repair process occurs by the formation of connective tissue but not dental pulp tissue per se .…”
Section: Introductionmentioning
confidence: 99%